An autonomously healable, highly stretchable and cyclically compressible, wearable hydrogel as a multimodal sensor. Issue 7 (10th January 2020) - Tie, Jianfei; Rong, Liduo; Liu, Hongchen; Wang, Bijia; Mao, Zhiping; Zhang, Linping; Zhong, Yi; Feng, Xueling; Sui, Xiaofeng; Xu, Hong
Abstract : Fe 3+ /PVAA-PAM hydrogels show highly stretchable, self-healing properties and can be used as artificial ionic skin for directly monitoring human motion. Abstract : Stretchable, self-healable, conductive hydrogels have received increasing attention due to their broad range of applications, such as wearable devices and ionic skin. However, severe challenges remain in integrating fatigue resistance, favorable self-healing, and stretchable and compressible efficiency into a hydrogel. Herein, a highly stretchable, compressible, self-healable somatosensory platform was fabricated by blending Fe 3+ ions with polyvinyl alcohol acetoacetate (PVAA)/polyacrylamide (PAM) hydrogel to form a double network hydrogel, which combined chemical coordination and physical crosslinking in one system. In this system, the PAM network offered high stretchability and compressibility to the hydrogel. Meanwhile, the coordination of the Fe 3+ /PVAA network provided ionic conductivity and self-healing ability. The resulting hydrogel exhibits prominent stretchability (>700%), high sensitivity, high healing efficiency (80% within 24 h) and excellent fatigue resistance. Therefore, the hydrogel could be used as a potential artificial ionic skin including strain and pressure sensors to directly monitor human motion.